Spirituality and Chaplaincy Supporting ICU Survivorship: A Practical Overview and Strategy for Clinicians - Ehman, John W. (Journal of religion and health, 2023)
This overview of the current literature of spirituality and health and the role of professional chaplains specifically considers intensive care unit survivorship, instead of the more common focus on end-of-life circumstances or family support on an ICU. The purpose is to enhance clinicians’ understanding and use of spiritual resources for patient care and outcomes. It is a product of comprehensive daily monitoring of the Medline database from 2002 to 2022 for all publications indexed by the terms "spiritual," "religion," and "chaplain." A case will be used throughout, to illustrate spirituality dynamics. Also, a practical strategy, developed by the authors from clinical experience, will be outlined for clinicians’ spiritual support of patients, requiring little time or specialized knowledge and avoiding the blurring of professional roles and boundaries, while potentially yielding clinical benefits suggested in the medical literature.